2019
DOI: 10.5539/jas.v11n5p250
|View full text |Cite
|
Sign up to set email alerts
|

Drying Kinetics of Noni Seeds

Abstract: Noni seeds have been used for years as an important medicinal source, with wide use in the pharmaceutical and food industry. Drying is a fundamental process in the post-harvest stages, where it enables the safe storage of the product. Therefore, the present study aimed to fit different mathematical models to experimental data of drying kinetics of noni seeds, determine the effective diffusion coefficient and obtain the activation energy for the process during drying under different conditions of air temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 17 publications
3
10
0
3
Order By: Relevance
“…Even though no reaction occurs while drying, the operation is not spontaneous and thus requires the additional energy for the moisture vaporization (D. E. C. de Oliveira et al, 2015). The results from the present work are in agreement with other works, such as Quequeto, Siqueira, Ferranti, Schoeninger, and Leite (2017)) for drying beans; Guimarães et al (2018) for drying Okara; Quequeto, Resende, Silva, Silva, and Silva (2019) for noni seeds. All works also found a reduction in the process enthalpy and an increase in Gibb's free energy.…”
Section: Resultssupporting
confidence: 93%
“…Even though no reaction occurs while drying, the operation is not spontaneous and thus requires the additional energy for the moisture vaporization (D. E. C. de Oliveira et al, 2015). The results from the present work are in agreement with other works, such as Quequeto, Siqueira, Ferranti, Schoeninger, and Leite (2017)) for drying beans; Guimarães et al (2018) for drying Okara; Quequeto, Resende, Silva, Silva, and Silva (2019) for noni seeds. All works also found a reduction in the process enthalpy and an increase in Gibb's free energy.…”
Section: Resultssupporting
confidence: 93%
“…Silva et al (2019a) studied white bean grains and observed that diffusivity increased from 3.46 to 10.30 × 10 −8 m 2 /min for temperature range from 40 to 80°C. Quequeto, Resende, Silva, Silva, and Silva (2019) obtained effective diffusivity ranging from 8.6968 to 23.7089 x 10 −10 m 2 /min for noni seeds. According to Carvalho, Bueno, Oliveira, and Resende (2018), the diffusivity depends on drying air temperature, that is, the higher the drying air temperature, the lower the resistance of the grain to water removal and the greater the diffusivity.…”
Section: Resultsmentioning
confidence: 98%
“…The values of Akaike Information Criterion (AIC) and Schwarz's Bayesian Information Criterion (BIC) were used as auxiliary to further refine the selection of the best model for representing the drying kinetics of buckwheat grains, considering the parameters of the models preselected according to Gauss-Newton criterion (Table 3). This criterion has been used previously for selecting models to represent the drying kinetics of various vegetable products, such as Piper aduncum L. leaves (Quequeto et al, 2019a), Morinda citrifolia L. grains (Quequeto et al, 2019b), and Ipomoea batatas L. pulp (Souza et al, 2019).…”
Section: Resultsmentioning
confidence: 99%